Lactic acid production from Sophora flavescens residues pretreated with sodium hydroxide: Reutilization of the pretreated liquor during fermentation. (October 2017) - Wang, Juan; Gao, Ming; Liu, Jianguo; Wang, Qunhui; Wang, Cong; Yin, Zihe; Wu, Chuanfu
Highlights: NaOH pretreatment enhanced the hydrolysis efficiency from 37.3% to 79.2%. Fermentation of SFR with 50% PL increased the lactic acid production by 34.1%. The PL stabilized the cellulase activity during the fermentation. The PL did not inhibit LAB growth, but inhibited the ethanol-producing yeast. Fermentation of unwashed SFR with 50% PL reduced the water consumption by 67.6%. Abstract: The feasibility of lactic acid production from Sophora flavescens residues (SFRs) pretreated with sodium hydroxide with the reutilization of the pretreated liquor during fermentation was investigated. After sodium hydroxide pretreatment, 67.5% of the lignin was removed, and hydrolysis efficiency increased from 37.3% to 79.2%. The reutilization of pretreated liquor at 50% loading during open fermentation of unwashed SFR increased lactic acid production by 34.1%. The pretreated liquor acted as pH buffer and resulted in stable pH and high cellulase activity during fermentation. Inhibitors in the pretreated liquor did not affect the growth of lactic acid bacteria but severely inhibited the growth of ethanol-producing yeast. Consequently, lactic acid production increased and ethanol production was zero at 50% loading. Water consumption during pretreatment and fermentation with 50% pretreated liquor was 1.341 L per 100 g SFR, which was 67.6% lower than that during fermentation with washed SFR.